The role of green bonds and green sukuk in sustainable finance: Challenges, impacts, and strategic recommendations - Wahab, Muhammad Zarunnaim; Mat Khairi, Siti Murni; Hanafi, Ahmad Harith Ashrofie; Mohd Saufi, Mohd Shahid Azim (International Journal of Accounting, Finance and Business, 2025)
Green bonds and sukuk have emerged as vital financial instruments for funding environmentally sustainable projects, particularly in Malaysia, where Islamic finance plays a significant role. Despite their potential to drive economic growth, support environmental goals, and enhance financial market maturity, the adoption of green bonds and sukuk faces several challenges, including a lack of standardized regulations, greenwashing risks, high issuance costs, and limited awareness among investors. This study employs a systematic literature review to analyze the challenges, economic and environmental impacts, and recommendations associated with green bonds and sukuk. The findings highlight the positive contributions of green bonds to economic diversification, job creation, and sustainable infrastructure development while also identifying key barriers that hinder their effectiveness. To address these challenges, the study recommends establishing clear regulatory frameworks, enhancing transparency through improved reporting standards, providing financial incentives, and promoting investor awareness. Strengthening these areas will enhance the credibility and accessibility of green bonds, fostering a more robust sustainable finance ecosystem. The study contributes to the ongoing discourse on sustainable finance by providing insights into the evolving landscape of green bonds and sukuk, particularly within emerging markets.